Faktor-Faktor yang Berhubungan dengan Gangguan Pendengaran Tipe Sensorineural Tenaga Kerja Unit Produksi PT.Kurnia Jati Utama Semarang - Arini, Evi Yulia; Setiani, Onny; Budiyono, Budiyono (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2005)
ABSTRACT Background : PT. Kurnia Jati Utama is a wood processing company. Noise intensity in production room was passing over the threshold limit value (TLV) 85 dB (A). Workers work continuously over 8 hours a day or even more. If that noise exposure expose for 8 hours a day or 40 hours a week, it will make a sensory neural hearing loss. The Objective of this research was to determine factors that related to SNHL on unit production workers of PT. Kurnia Jati Utama. Methods : The research design used cross - sectional approach. Populations of this research were workers at unit sawmill, garden furniture and moulding. Respondents were determine by inclusion criteria, and it was choose 60 workers. Data was analyzed using univariate technique with frequencies distribution table, bivariate by chi-square and multivariate analysis by logistic regression. Result The result of the study showed that 23 respondents (38.3%) had sensory neural hearing loss 39 respondents ( 65%) had noise exposure more over 85 dB ( A);30 respondents (60%) have age of more than 30 year; 35 respondents ( 58,3%) had been work less than 10 year; 45 respondents ( 75%) works over 8 hours a day and 40 hours a week; 51 respondents ( 85%) didn’t wear ear protector. There was a significant relation between noise intensity, years of work and working hours with sensor neural hearing loss incidence. There was no relation between age and using self protector equipment with sensory neural hearing loss incidence; (9) There was a significant relation between noise intensity, years of work and working hours ( by together) with sensory neural hearing loss incidence Conclusions : Workers who have been working for more than 10 years, and works over 8 hours a day or 40 hours a week and expose the noise more than 85 dB (A), have 98,8% risk of sensory neural hearing loss risk. Key Words : Noise, SNHL, Wood Industry Workers